Comparative Legal Analysis of the Use of Electronic Format of Criminal Cases and the Procedure under the Code of Criminal Procedure of the Russian Federation - Dmitriy Ivanov; Aleksandr Grinenko; Pavel Fadeev; Sergey Ermakov; Svetlana Antimonova (Jurnal Cita Hukum, 2024)
The article deals with foreign experience of digitalization of preliminary investigation. Russian Federation is dominated by conservative views of law enforcers and legislators on this issue. Currently there are only small steps towards the digitalisation of preliminary investigation in our country. At the same time it has been established that the introduction of various information systems and automated workstations into practice, which was supposed to create a unified system and network of wide coverage, has not happened due to the lack of a unified request from the system of investigative bodies and technical capabilities, as well as lack of an urgent need for changes in the working procedure on the part of investigators and interrogators. In conclusion, the authors conclude that there are currently only minor steps towards digitalisation of pre-trial investigations and the creation of an electronic format for criminal cases in the Russian Federation. However, it is obvious that the rapidly developing information and telecommunication technologies will do their job in this aspect as well, which will lead to the creation and successful testing of the topic studied by the authors.